2023
DOI: 10.3389/fgene.2023.1138230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hsa-miR-619-5p and hsa-miR-4454 in plasma-derived exosomes as a potential biomarker for lung adenocarcinoma

Abstract: Introduction: Lung cancer has long been at the forefront of all cancers in terms of incidence and mortality. Lung adenocarcinoma is the most common type of lung cancer, accounting for 40% of all lung cancer types. Exosomes can act as biomarkers of tumors and thus play an important role.Methods: In this article, high-throughput sequencing of miRNAs in plasma exosomes from lung adenocarcinoma patients and healthy individuals was performed to obtain 87 upregulated miRNAs, which were then combined with data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…To date, substantial studies reported that exosome is a non-invasive, sensitive, and specific biomarker in the tumor’s occurrence and development. has-miR-619-5p ahashsa-miR-4454 in plasma-derived exosomes have the potential to be used as biomarkers for the early diagnosis of lung adenocarcinoma ( 17 ). Exosomal circ_0009910 regulates proliferation, cell cycle, and apoptosis of acute myeloid leukemia cells by interfering with the miR-5195-3p/GRB10 axis ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, substantial studies reported that exosome is a non-invasive, sensitive, and specific biomarker in the tumor’s occurrence and development. has-miR-619-5p ahashsa-miR-4454 in plasma-derived exosomes have the potential to be used as biomarkers for the early diagnosis of lung adenocarcinoma ( 17 ). Exosomal circ_0009910 regulates proliferation, cell cycle, and apoptosis of acute myeloid leukemia cells by interfering with the miR-5195-3p/GRB10 axis ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain exosomal miRNAs found in plasma or serum exhibit high expression levels in NSCLC, thus serving as specific biomarkers for its diagnosis and prognosis ( Table 1 ). Notably, the exosomal miR-146a-5p/miR-486-5p ( Wu Q. et al, 2020 ), miR-619-5p/miR-4454 ( Feng et al, 2023 ), miR-21/miR-25/miR-155/miR-210/miR-486 ( Liu et al, 2020 ) and EV-miR-486-5p/miR-21-5p ( Tong et al, 2024 ) were upregulated in NSCLC patients than in healthy people. The high expression of these three panels EV-miRNAs is positive correlation with NSCLC diagnosis.…”
Section: Exosomal Mirnas As Potential Biomarkers For the Treatment Of...mentioning
confidence: 99%